Covalent organic framework wrapped by graphene oxide as an efficient sulfur host for high performance lithium–sulfur batteries. (28th May 2022) - Hu, Zongjie; Yan, Gaojie; Zhao, Jinchen; Zhang, Xiaojie; Feng, Yi; Qu, Xiongwei; Ben, Haijie; Shi, Jingjing
Abstract: The practical application of lithium–sulfur battery is seriously limited by the loss of active substances and the deterioration of cycle stability caused by the 'shuttle effect' of lithium polysulfides (LiPSs). In this work, graphene oxide (GO) coated covalent organic framework (COF) compound materials were synthesized as sulfur host material in spray-drying process. The polar groups on COF can efficiently adsorb LiPSs through lithiophilic interaction, which can reduce the 'shuttle effect' caused by soluble LiPSs. Besides, GO in the outer layer can wrap discrete sulfur to reduce the loss of active substances, which further improves the cycle stability of the cathode. The COF@GO/S cathode exhibits a high initial specific capacity of 848.4 mAh g −1 and retains a capacity of 601.1 mAh g −1 after 500 cycles at 1 C counting with a low capacity fading of 0.058% per cycle.